Volatile, stored and phloem exudate-located compounds represent different appearance levels affecting aphid niche choice. (March 2019) - Jakobs, Ruth; Müller, Caroline
Abstract: Intraspecific and intra-individual differences in emitted volatile compounds and in surface and phloem sap-related metabolites do not only affect host plant choice of monophagous aphids but may also guide them to the plant part that provides their ideal niche by maximising their fitness. However, little is known about the variation at these different plant appearance levels. We investigated the preferences of the monophagous aphid species Macrosiphoniella tancetaria and Uroleucon tanaceti for different plant parts (inflorescence stems, young and old leaves) of Tanacetum vulgare plants from two chemotypes, testing their reactions towards volatile, surface and phloem sap-related cues. Furthermore, we studied the variation in leaf glandular trichome density as well as in the composition of volatile, stored and phloem exudate-located specialised (secondary) plant compounds from the different plant parts of these chemotypes. Aphid species showed differences in their preferences. Aphids of M. tanacetaria had to assess the entire plant to choose the stem, whereas U. tanaceti only needed volatile cues to locate the old leaves, which are the plant parts representing their respective niches. Volatiles and stored metabolites varied in their composition and concentration between chemotypes. Stored metabolites additionally differed among plant parts, which was reflected in distinct trichome densities. The composition of phloem exudate-located specialised compounds mostly varied among plant parts. These pronounced differences in plant chemistry on multiple levels provide distinct perception levels for aphids probably driving their niche choice. This study demonstrates the importance to consider these multiple levels to elucidate plant-herbivore interactions with high resolution. Graphical abstract: Highlights: Effects of phytochemical variation on niche choice of two aphid species are studied. Aphids recognise their species-specific niches guided by distinct cues. Chemical composition differs between and within individuals of host plants. Variation also found between emitted, stored and phloem exudate-located metabolites. Study highlights importance to investigate plant variation at multiple levels.